Pengaruh dan Makna Sosial Pemberian Julukan (Laqob) terhadap Solidaritas Antarsantri di Pondok Pesantren: Kajian Sosiolinguistik - Ahmad Afallah; Syafi' Junadi (JP-BSI (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2026)
This study aims to analyze the influence of nicknames (laqob) on the level of solidarity among students in Islamic boarding schools. The phenomenon of laqob in Islamic boarding schools has two sides, namely as a social glue through symbolic communication or as a potential trigger for conflict and verbal bullying. This study uses a mixed methods approach with a sequential explanatory design. Quantitative data were obtained from 36 male student respondents at the Darussalam Islamic Boarding School Dormitory, Blokagung using a Likert scale questionnaire, which was then analyzed using simple linear regression. The qualitative stage was carried out through observation and in-depth interviews to explore the symbolic meaning behind the practice. The results of this study indicate that the giving of laqob has a positive and significant influence on student solidarity with a significance value of 0.000 < 0.05 and a t-value of 4.700 > t-table of 2.032. The variable of giving laqob is able to explain the variation in student solidarity by 39.4%. Qualitative findings reveal the existence of a "reinterpretation mechanism" where potentially negative nicknames are transformed into symbols of familiarity, group identity, and unique brotherhood within the Islamic boarding school environment. This study provides a novel contribution to sociolinguistic research within Islamic boarding school environments by demonstrating a mechanism of semantic reclamation, wherein students collectively neutralize the potential negative impacts of verbal bullying from nicknaming (laqob) and transform them into endearment terms that signify in-group identity.